Infrastructure and Inclusive Economic Growth in Decentralized Indonesia - Kurniasih, Dwi Esti (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
This research investigates the impact of decentralization in the link between infrastructure and inclusive economic growth in Indonesia. It address the question of whether decentralization strengthens the relationship between infrastructure and inclusive economic growth or not. Structural Equation Modelling (SEM) analysis is applied to explain those relationship. Data were collected from several publications issued by Indonesian Central Statistics Agency (BPS). It contains both secondary data and the result of national survey from 2013 to 2017. The findings show that the effectiveness of decentralization in Indonesia is vary among regions. The result of the statistical test—PLS SEM—shows that the relevance between decentralization and inclusive economic growth is significant in Indonesia case and Sulawesi-Nusa Tenggara-Papua, but is insignificant in Sumatra, Java-Bali, and Kalimantan. While in the context of the relationship between infrastructure and inclusive economic growth, it was positively and significant in Sumatra and Kalimantan but insignificant in Indonesia case, Java-Bali, and Sulawesi-Nusa Tenggara-Papua. As the result of main hypotheses, this research conclude that decentralization does not matter yet in strengthen relationship between infrastructure and inclusive economic growth in Indonesia.